Standortalternativen für die Windenergie – Berechnung des Ertragspotenzials auf Offenland- und Waldstandorten in Bayern - Ludwig, Nikolas; Bosch, Stephan (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
The consideration of alternative sites for renewable energies should not only be a reaction to dwindling acceptance of the transformation of the energy system. Rather it should be incorporated at the beginning of any site planning process and thereby enable transparent, democratic negotiations about sustainable land use. On the one hand, alternative sites can result from successively expanding or limiting the search area for sites by mini- or maximizing restriction criteria. On the other hand, a certain search area may be extended by considering a category of space not previously included in the site calculation process. Both aspects will be discussed in the following attempt to develop spatial corridors for the implementation of the transformation of the Bavarian wind energy system. The spatial patterns resulting from the GIS-based site analysis for wind power plants may serve as a basis for the allocation of exclusion, restriction, and priority areas in regional planning. Simply standardizing procedures among the various regional planning associations based on potential analysis may prevent a patchwork of energy strategies and may guide site planning processes towards a balanced spatial development. It is the main goal of this study to investigate the suitability concerning usage for wind power of sites on both open landscapes as well as in forest territories. Thereby those spatial patterns of wind power are being identified that not only meet the specifications of the “bavarian wind decree”, but furthermore satisfy the qualitative demand for a maximum socio-ecological compatibility.